“You Took My Spirit Captive among the Leaves”: The Creation of Blodeuwedd in Re-Imaginings of the Fourth Branch of the Mabinogi - Bartels-Bland, Cara (Pomegranate, 2015)
This article traces the portrayal of Blodeuwedd’s creation, the woman fashioned from flowers in the Fourth Branch of the Mabinogi, from the medieval version to twentieth and twenty-first century retellings of the story. Blodeuwedd’s creation will be situated in the wider context of the idea of the automaton and will be read as a posthuman construct, eerily relevant in today’s cybernetic society. The symbolism of the flowers from which she is created will be analyzed and the curious alignment of flowers to Sexuality, non-existent in the medieval text but exceedingly prominent in the modern versions, will be explored. This article will concentrate on mainly three works, which present diverse re-imaginings of the medieval material: Saunders Lewis’ Blodeuwedd, Alan Garner’s The Owl Service and Gwyneth Lewis’ The Meat Tree.